2012
DOI: 10.1007/s00787-012-0320-7
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy in adolescents with intellectual disability and severe self-injurious behavior and aggression: a retrospective study

Abstract: Efficacious intervention for severe, treatment-refractory self-injurious behavior and aggression (SIB/AGG) in children and adolescents with intellectual disability and concomitant psychiatric disorders remains a complex and urgent issue. The aim of this study is to assess the efficacy of electroconvulsive therapy (ECT) on severe and treatment-resistant SIB/AGG in young people with intellectual disability and current psychiatric disorder. We reviewed the charts of all patients (N = 4) who received ECT in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 66 publications
0
32
0
1
Order By: Relevance
“…In fact, in recent years large population-based studies have estimated that 12-18% of autistic adolescents and young adults manifest some symptoms of catatonia (Billstedt et al, 2005;Ghaziuddin et al, 2012;Wing and Shah, 2000). Consistent with the sensitivity of catatonia to electroconvulsive therapy (ECT; Fink and Taylor, 2006), we and others have found ECT can produce life-changing results in ASD patients with extreme SIB that is unresponsive to traditional pharmacological and behavioral therapies (Wachtel and Dhossche, 2013;Consoli et al, 2013;Haq and Ghaziuddin, 2014). At our clinic, we have observed a 490% reduction in frequency of SIB in ASD patients with the most severe forms of self-injury (Wachtel et al, 2008(Wachtel et al, , 2009(Wachtel et al, , 2010(Wachtel et al, , 2014(Wachtel et al, , 2015.…”
Section: Introductionmentioning
confidence: 80%
“…In fact, in recent years large population-based studies have estimated that 12-18% of autistic adolescents and young adults manifest some symptoms of catatonia (Billstedt et al, 2005;Ghaziuddin et al, 2012;Wing and Shah, 2000). Consistent with the sensitivity of catatonia to electroconvulsive therapy (ECT; Fink and Taylor, 2006), we and others have found ECT can produce life-changing results in ASD patients with extreme SIB that is unresponsive to traditional pharmacological and behavioral therapies (Wachtel and Dhossche, 2013;Consoli et al, 2013;Haq and Ghaziuddin, 2014). At our clinic, we have observed a 490% reduction in frequency of SIB in ASD patients with the most severe forms of self-injury (Wachtel et al, 2008(Wachtel et al, , 2009(Wachtel et al, , 2010(Wachtel et al, , 2014(Wachtel et al, , 2015.…”
Section: Introductionmentioning
confidence: 80%
“…ECT is thought to treat SIB by affecting underlying GABA dysfunction. Several case studies have reported significant reductions in drugrefractory SIB, along with mood stabilization, with ECT (Consoli et al 2013;Siegel et al 2012;Wachtel et al 2009. Studies of ECT are promising in the appropriate context as a potential treatment, and future studies will aid in defining its role in the treatment of drug-refractory SIB.…”
Section: Electroconvulsive Therapymentioning
confidence: 97%
“…Electroconvulsive therapy (ECT) has been used as a treatment for drug-refractory SIB in individuals with ASD and other developmental disorders who have catatonia or a concurrent psychiatric disorder (Consoli et al 2013;Wachtel and Dhossche 2010). ECT is thought to treat SIB by affecting underlying GABA dysfunction.…”
Section: Electroconvulsive Therapymentioning
confidence: 99%
“…In such treatment refractory clinical situations, alternative strategies must to be defined and tested. Using electro-convulsive therapy may be considered, for example in cases of severe self-injurious behavior and aggression [3].…”
mentioning
confidence: 99%